Bajocian ammonites from Msata hill (Lugoba formation) in the hinterland of Dar es Salaam, Tanzania - Kapilima , S (Tanzania Journal of Science, 2021)
Ammonites from the Middle Jurassic exposures of the Lugoba Formation at Msata, are described for the first time in Tanzania. Out of a number of ammonite fragments recovered from the bluish-green silty limestone (M3), only three fragments were fairly well preserved to permit their specific identification. Two species were identified: Dorsetensia cf. D. romani (OPPEL) and Oecotraustes (Paroecotraustes?) cf. angustus DOUVILLE. This ammonite assemblage is biostratigraphically correlatable with the Lower Bajocian Posidonia shale of the Kambe Limestone series in Kenya, in which similar ammonites species and other related Bajocian species have been described. Pending new discovery of ammonoid fauna and other guide fossils, on the basis of this ammonite evidence, the Lugoba Formation is reasonably assigned to the Humphrieasianum – Zone of the Lower Bajocian